Comparison of the Ramirez technique for the closure of large open myelomeningocele defects with alternative methods - Kneser, Ulrich; Bigdeli, Amir K.; Himmler, Joerg P.; Eyüpoglu, Ilker Yasin; Ganslandt, Oliver Thomas; Hirsch, Almut; Schmidt, Volker J.; Beier, Justus; Horch, Raymund E. (Journal of Plastic Reconstructive and Aesthetic Surgery, 2015)
To compare the Ramirez technique for the operative closure of large open myelomeningocele defects with conventional closure techniques in newborns. We hypothesized that the immediate surgical treatment with the Ramirez technique is superior to prior used operative techniques.From 2003 to 2010, 23 children (8 female, 15 male) underwent closure of large open myelomeningocele defects using the Ramirez technique (group A), while from 1993 to 2002, 23 children (6 female, 17 male) underwent conventional closure techniques (group B). All children were included in the retrospective analysis with a mean follow-up period of 3.4 years.Perioperative variables were similar in both groups (P = ns). There were no hospital deaths in both groups. The operation time was significantly higher in group A (228.7 ± 76.8 versus 157.8 ± 70.3 min, P = 0.003). Mean length of hospital stay was significantly lower in group A (30.7 ± 16.4 days versus 52.0 ± 38.5; P = 0.02). Postoperative complication rate was significantly lower in group A (P = 0.01). Beyond postoperative day 10, liquor fluid leakage was significantly lower in group A (P = 0.05). During follow-up, there were no complications in group A. In group B, 2 children developed liquor fistulas.The Ramirez technique allows efficient and safe closure of large open myelomeningocele defects and reduces incidence of postoperative liquor fistulae. The increased operation time and surgical efforts seem to be justified. Treatment of large myelomeningocele defects requires an interdisciplinary team including paediatrician-neonatologists, neurosurgeons and plastic surgeons.
EVALuna2:15600